Experiences and counseling needs of men having sex with men with hiv - Lee, Eddy Kok Leong (2013)
This qualitative study aimed at exploring the experiences of MSM (men who have sex with men) Living with HIV draw on the theory of Shattered Assumptions by Januff-Bulman. The theory of Shattered Assumptions believes people have falsely assumed that their world is benevolence and secure. These false assumptions are shattered when they experience a traumatic event. However, individuals whose old assumptions were shattered managed to rebuild their inner world with support from loved ones and friends. More positive and realistic assumptions will transpire once they have adjusted to their post-traumatic world. The PCC perspective sees human beings as possessing the self-actualizing tendency and constantly in the process of “becoming”. Given an environment of acceptance, positive and empathic, the human person will utilize his/her self-actualizing tendency to cope and adjust in any adverse situation and condition. Five HIV positive MSM (men who have sex with men) who volunteered to participate in this study were interviewed using a semi-structured interview guide. These participants were selected from a HIV positive support group. The interview data collected were transcribed into verbatim and analyzed using the constant comparative method. Content analysis of the first transcripts, field notes and document collected yielded meaningful units and subthemes. Four main themes emerged from the data collected based on the first two research questions,namely, life, relationship with family, relationship with friends, and purpose, religion and spirituality. Twenty three sub-themes were derived from the four main themes. The three major changes in the lives of the participants based on the data were they had become better people,they discovered the purpose of their life and their relationship with their family had improved. Though the participants had contracted a treatable but fatal disease, none of them was afraid of death. In fact, they viewed death as something inevitable and natural. Six main themes emerged from the data collected in research question three and they were the counseling need of information, the counseling need of support, the counseling need of expressing feelings and thoughts, the counseling need of guidance, the counseling need of hope,the counseling need of acceptance. The findings of the study implied that Januff-Bulman’s theory of Shattered Assumptions and Carl Roger’s PCC theory are relevant in the understanding of the experiences of PLHIV as well as their counseling needs. In addition, PCC’s three core conditions are also appropriate to promote growth in the counselor to enhance his/her counseling competency, especially in helping PLHIV clients. The study also showed that support groups were the most appropriate to meet PLHIV counseling needs. Further studies are recommended to include experiences of PLHIV from the straight community, men and women as well as communities from the different ethnic groups in the Malaysian society.